Total Management: A Case Of Tribhuvan University - Thakur, Arun Kumar (Tribhuvan University Journal, 2019)
Total management refers to managing all elements/components and resources of the organization through analyzing the environmental situations and carrying out SWOT analysis so that the system of smooth operation can be ensured to accomplish the organizational goals. This article has analyzed the problems of T.U. under three components (i.e. teachers, staffs and students) with reference to the allocated resources (i.e. human, financial, physical and informational). Three major problems were identified separately through factor analysis which covers more than80% of the problems related to each component and resources. The study shows that there are three major causes of all the problems in T.U. They are: Firstly, the appointment of executives, teachers and staffs is not done on the basis of senerioty and quality and placement of right kind of manpower are not made on the basis of the requirement of the job to be per formed in efficient and effective manner. The second major cause is lack of commitment of employees towards their job (i.e. lack of dedication, devotion, determination and discipline). The third major cause is the dissatisfaction of employee in terms of salary, incentives, reward, and punishment.